Legal Principles of Evidence on Civil Cases in Public Judiciary - Dwi Handayani (Hang Tuah Law Journal, 2017)
Legal principles in civil procedure law apply to the process of evidence as well, including ‘Audit et alteram partem’ principle which mentions that litigants’ testimony must be presented in hearing session. Based on article 163 HIR/283 RBg, the plaintiff proves with evidence. The judge will make a judgment and through this evidence proceeding, the judge needs to seek for the real evidence disputed both parties in order to make a fair and impartial judgment as the mandate of ‘Audi et alteram partem’ principle. Comparison between the process and the system of evidence on private cases in Anglo-Saxon country (Singapore) is quite similar in the processes. Compared with Indonesia, however, the system of evidence in Singapore seems more ‘open’, while the system in Indonesia is ‘closed’ in its nature. The openness is on broader submission of evidence (not limited to what has been set on the constitution). In the contrary, the system of evidence in Indonesia is restricted by the law (article 164 HIR/284 RBg) and judges only engage on what both parties have submit. This research tries to identify the similarity and the difference on legal principles of evidence among Indonesia, Netherlands and Singapore.